2020
DOI: 10.1155/2020/4683798
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype Analysis of Candidate Genes Involved in Inflammation and Oxidative Stress and the Susceptibility to Preeclampsia

Abstract: Unbalanced inflammatory reactions and oxidative stress are inseparably interconnected, and both may play crucial roles in the pathophysiological mechanisms of preeclampsia (PE). In the published previous studies, we have genotyped for SNPs that related to inflammation (rs2227485, rs153109, rs17855750, rs2027432, rs2275913, rs763780, rs4819554, and rs13015714) and oxidative stress (rs1695, rs4680, rs1800566, rs4807542, rs713041, rs7579, rs230813, rs1004467, rs3824755, and rs9932581) to investigate whether these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…It has been reported that the interleukin-33 SNP rs1888909 is associated with an increased risk of hay fever in high linkage disequilibrium via interaction with rs928413 and rs1342326 [32]. The GPX4 SNP rs4807542 was reported to be associated with Kashin-Beck disease, biliary tract cancer, and preeclampsia in a Chinese Han population [33][34][35]. To date, few studies have investigated SNPs rs1444782, rs338598, rs6543124, rs8046011, rs28383314, and rs62408225.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the interleukin-33 SNP rs1888909 is associated with an increased risk of hay fever in high linkage disequilibrium via interaction with rs928413 and rs1342326 [32]. The GPX4 SNP rs4807542 was reported to be associated with Kashin-Beck disease, biliary tract cancer, and preeclampsia in a Chinese Han population [33][34][35]. To date, few studies have investigated SNPs rs1444782, rs338598, rs6543124, rs8046011, rs28383314, and rs62408225.…”
Section: Discussionmentioning
confidence: 99%
“…Although the association of IL17A polymorphism with reproduction traits has been scarcely studied, a previous study has demonstrated that the human IL17RA (rs4819554) polymorphism is associated with the pregnancy disorder of preeclampsia in a Chinese Han population (Chen et al, 2020). Conversely, there is no association of the human IL17RA polymorphism with preeclampsia in Chinese women (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL17 and IL17R are implicated in various reproductive processes including implantation, placentation, and maintenance of pregnancy (Pongcharoen et al, 2006;Pongcharoen and Supalap, 2009;Saito et al, 2011). Genetic polymorphisms and abnormal expression of IL17 and/or IL17R are associated with the pregnancy disorders of preeclampsia, recurrent implantation failure, and recurrent pregnancy loss in women (Najafi et al, 2014;Zidan et al, 2015;Wang et al, 2019;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is defined as an imbalance between oxidants and antioxidants in the body, 9 that induces endothelial dysfunction, poor placental perfusion, and systemic inflammatory responses 66 . Evidence has also supported the involvement of oxidative stress in the activation nuclear factor kappa‐B (NF‐κB) pathway, which can promote the release of inflammatory factors and adhesion molecules ultimately affecting involved in the occurrence of PIH 9 …”
Section: Genetic Polymorphisms Of Pihmentioning
confidence: 99%